COX-2 Inhibitors and Gastric Cancer - Zhen Wang; Jun-qiang Chen; Jin-lu Liu (Gastroenterology Research and Practice)
The evidence that cyclooxygenase-2 (COX-2) is upregulated and plays an important role in carcinogenesis of gastric cancer has triggered the topic of COX-2 inhibitors as chemopreventive agents for gastric cancer. Studies find that COX-2 inhibitors are associated not only with chemoprophylactic effects, but also with chemotherapeutic potentials in gastric cancer. Both COX-dependent and COX-independent pathways have a role in the anticancer efficiency of COX-2 inhibitors. However, enthusiasm is thwarted by the potential toxicity, that is, gastrointestinal toxicity of nonselective COX-2 inhibitors and cardiovascular risk of selective COX-2 inhibitors. Therefore, more studies are needed to develop new targeted antitumor agents (such as prostaglandin E receptor antagonist) and to define fundamental questions such as optimal treatment regimens, integration of cotherapy, and careful selection of candidates.